2012
DOI: 10.3390/ijms13033245
|View full text |Cite
|
Sign up to set email alerts
|

Use of the MLPA Assay in the Molecular Diagnosis of Gene Copy Number Alterations in Human Genetic Diseases

Abstract: Multiplex Ligation-dependent Probe Amplification (MLPA) assay is a recently developed technique able to evidence variations in the copy number of several human genes. Due to this ability, MLPA can be used in the molecular diagnosis of several genetic diseases whose pathogenesis is related to the presence of deletions or duplications of specific genes. Moreover, MLPA assay can also be used in the molecular diagnosis of genetic diseases characterized by the presence of abnormal DNA methylation. Due to the large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
148
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(154 citation statements)
references
References 163 publications
(118 reference statements)
0
148
0
6
Order By: Relevance
“…The MLPA technique is a powerful tool for evaluating genetic deletions that cannot be detected using PCRbased sequencing techniques. The MLPA assay has been adapted to detect aberrant methylation (19). Methylation-sensitive (MS)-MLPA is a modification of the MLPA assay with a methylation-sensitive restriction endonuclease that simultaneously detects the methylation state of CpG islands.…”
Section: Introductionmentioning
confidence: 99%
“…The MLPA technique is a powerful tool for evaluating genetic deletions that cannot be detected using PCRbased sequencing techniques. The MLPA assay has been adapted to detect aberrant methylation (19). Methylation-sensitive (MS)-MLPA is a modification of the MLPA assay with a methylation-sensitive restriction endonuclease that simultaneously detects the methylation state of CpG islands.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, MLPA was efficient in accurately confirming mutations in about 67% of all the cases. A number of studies have found MLPA assay to be highly sensitive diagnostic assay to identify mutation in DMD and BMD patients [9]. In the study to evaluate the efficacy of MLPA technique in comparison with the traditional multiplex PCR assay in detection of exon deletions and duplications of the DMD gene by Lai et al, MLPA was able to detect all the known deletions and duplications; it detected four additional mutations that had been missed by multiplex PCR [10].…”
Section: Discussionmentioning
confidence: 99%
“…The utility of MLPA assay in the testing of acute leukemias and myelodysplastic syndromes has been analyzed, confirming excellent accuracy and specificity of MLPA as compared to FISH (ref. 39 ). The SALSA MLPA MDS kits (P144 and P145, MRC Holland) are used to detect chromosomal abnormalities commonly associated with MDS.…”
Section: Multiplex Ligation-dependent Probe Amplification (Mlpa)mentioning
confidence: 99%